Genomic Features of Organ-Specific Metastases in Lung Adenocarcinoma - Feng, Alei; Li, Yanjun; Li, Guangxu; Wang, Yu; Wen, Qiang; Yang, Zhe; Tian, Kaihua; Lv, Hongying; Guo, Lijie; Zhang, Shanshan; Liu, Xiaoyan; Jiang, Da (Frontiers in Oncology, 2022)
Background The genomic features of cancer cells may confer the metastatic ability of lung adenocarcinoma (LUAD) to metastasize to specific organs. We aimed to identify the differences in genomic alterations between patients with primary LUAD with and without metastases and to elucidate the metastatic biology that may help developing biomarker-directed therapies for advanced or metastatic disease. Methods A retrospective cohort of 497 patients with LUAD including 388 primary tumors (PR), 53 bone metastases (MT-bone), 30 liver metastases (MT-liver), and 26 brain metastases (MT-brain) was tested for genomic alterations by a next-generation sequencing assay. Results The EGFR, TP53, TERT, LRP1B, CDKN2A, ERBB2, ALK, and KMT2C genes had a high frequency of mutations, and the mutations were shared by PR and metastases groups. TP53 and EGFR were the most common mutated genes. In comparison with PR, KRAS, STK11, ATM, NPM1, and ROS1 were significantly mutated in MT-brain, and TP53, MYC, RSPO2, CDKN2a, and CDKN2B were significantly mutated in MT-liver. The frequencies of TP53, CDKN2A, MTAP, PRKCI, and APC mutations were higher in MT-bone than that in PR. The ERBB, phosphoinositide-3-kinase/protein kinase B (PI3K-AKT), cell cycle, Fibroblast growth factor (FGF), and homologous recombination deficiency signaling pathways were affected in both PR and metastases, and there is higher frequency of mutations in metastases. Moreover, the co-mutations in patients with PR and metastasis were respectively analyzed. In addition, the programmed death ligand 1 (PD-L1) level was obviously related to tumor stage and tumor metastases, and the tumor mutational burden was correlated to clinicopathological features including age, gender, pathological stages, and tumor metastases. FGFR1, KAT6A, MYC, RAD21, TP53, and DAXX were also dramatically correlated to the tumor mutational burden. Conclusion Metastases are the most devastating stage of tumors and the main cause of cancer-related deaths. Our results provided a clinically relevant view of the tumor-intrinsic mutational landscape of patients with metastatic LUAD.